Disturbing Business Ethics : Emmanuel Levinas and the Politics of Organization. - Rhodes, Carl (Milton : Routledge, 2019)
21st century Western neoliberalism has seen the transformation of self-interest from an economic imperative to a centrally constitutive part of dominant modes of subjective existence. Against this celebration of competitive individualism, Emmanuel Levinas' philosophy stands as a haunting reminder of an ethics that passively disturbs the self from its egoistic slumber, awakening it to the incessant demands of the other. Ethics stands as an anxious affective state of being where one is held to account by others, each one demanding care, attention and respect. Focussing on business activities and organizations, this book explores how this ethical demand of being for the other becomes translated, in a necessarily impure way, into political action, contestation and resistance. Such a response to ethics invokes a disturbance of organizational order, including an order that might itself be labelled ethical'. On these grounds, the book offers an explication of an ethics for organizations which disturbs the selfishness of neoliberal morality, and can inform a democratic politics rested on a genuine concern for the other and for justice. Disturbing Business Ethics: Emmanuel Levinas and the Politics of Organization offers an unconventional and enlightening approach to ethical thinking and practice in politics and organisations, and will be of interest to students of business, management, leadership, political science and organizational theory.
OCLC-licensed vendor bibliographic record.
Keywords: Lévinas, Emmanuel; Business ethics; BUSINESS & ECONOMICS -- General